Application of Target Costing as a Production Cost Control System to Increase Profits in the Nanda Roasted Bean Business - Tiara Syaloom Louishana Sondakh; Rudy Johanis Pusung; Sherly Pinatik (PT FORMOSA CENDEKIA GLOBAL, 2025)
Costing goals are a strategic approach that allows companies to price products in reference to acceptable costs, with the aim of increasing profitability. This study aims to determine the implementation of the target costing approach through handling manufacturing costs to increase profits in the Nanda Roasted Bean Business. The research approach applied is qualitative descriptive through an interview approach. The results of the analysis show that with the implementation of the costing target, the manufacturing cost through one year required is Rp 364,400,000, which generates a profit of 25.02%. On the other hand, the implementation of the traditional approach caused the manufacturing cost to increase to Rp 369,890,000, with profit falling to 23.89%. The difference of Rp 5,490,000 between these two approaches highlights the advantages of costing targets through controlling costs and maximizing profitability.